Phospho-Mimetic Mutation at Ser602 Inactivates Human TRPA1 Channel - Barvikova, Kristyna; Barvik, Ivan; Sinica, Viktor; Zimova, Lucie; Vlachova, Viktorie (International journal of molecular sciences, 2020)
The Transient Receptor Potential Ankyrin 1 (TRPA1) channel is an integrative molecular sensor for detecting environmental irritant compounds, endogenous proalgesic and inflammatory agents, pressure, and temperature. Different post-translational modifications participate in the discrimination of the essential functions of TRPA1 in its physiological environment, but the underlying structural bases are poorly understood. Here, we explored the role of the cytosolic N-terminal residue Ser602 located near a functionally important allosteric coupling domain as a potential target of phosphorylation. The phosphomimetic mutation S602D completely abrogated channel activation, whereas the phosphonull mutations S602G and S602N produced a fully functional channel. Using mutagenesis, electrophysiology, and molecular simulations, we investigated the possible structural impact of a modification (mutation or phosphorylation) of Ser602 and found that this residue represents an important regulatory site through which the intracellular signaling cascades may act to reversibly restrict or "dampen" the conformational space of the TRPA1 channel and promote its transitions to the closed state.
Keywords: simulace molekulární dynamiky; mutace; TRP channel; TRPA1 Cation Channel; HEK293 buňky; fosforylace; Phosphorylation; Molecular Dynamics Simulation; HEK293 Cells; mutagenesis; molekulární modely; proteinové domény; Models, Molecular; phosphorylation; lidé; konformace proteinů; Humans; kationtový kanál TRPA1; Protein Conformation; Mutation; phosphomimetic; Protein Domains; Serine; protein kinases; transient receptor potential ankyrin 1; serin